Impact of the COVID-19 Epidemic on Inhalant Allergen Sensitization in Children - Xueshan Huang; Min Yang; Ma Ye; Jun Qiu; Yanping Chen (Journal of Immunology Research)
Objective. To explore the impact of non-pharmacological interventions on inhaled allergen sensitization in children during the COVID-19 pandemic. Methods. The positive rate of inhaled allergens, allergens sIgE grade, and multiple sensitization rates before and during the pandemic were analyzed retrospectively in this study. Logistic regression analysis was used to compare the positive rate of allergens before and during the pandemic, using odds ratio (OR) and OR 95% CI to investigate the impact of the pandemic on allergen sensitization. Results. Positive rates of d1 (49.5% vs. 38.5%), d2 (50.2% vs. 32.2%), e2 (10.1% vs. 6.1%), e1 (6.2% vs. 1.7%), mx2 (10.1% vs. 2.7%), sycamore (7.2% vs. 2.1%), w1 (4.0% vs. 1.7%), elm (3.1% vs. 0.6%), w6 (3.0% vs. 1.7%), and u80 (1.3% vs. 0.5%) increased significantly during the COVID-19 pandemic. After adjusting gender, age, season, and other potential influencing factors, the COVID-19 pandemic was found to be a risk factor for the positive rate of d1 (OR = 1.174, 95% CI = 1.015–1.358), d2 (OR = 1.301, 95% CI = 1.093–1.549), e2 (OR = 1.499, 95% CI = 1.280–1.756), mx2 (OR = 3.959, 95% CI = 3.358–4.446), w1 (OR = 1.828, 95% CI = 1.353–2.470, w6 (OR = 1.538, 95% CI = 1.123–2.106)), and u80 (OR = 2.521, 95% CI = 1.413–4.497) (P<0.05). In addition, d1 and d2 allergen sIgE grades increased during the COVID-19 pandemic (d1: χ2 = 9.576, P<0.05; d2: χ2 = 39.063, P<0.05). The proportion of multiple allergies was significantly higher than that before the pandemic, with a statistical significance (χ2 = 1621.815, P<0.05). Conclusion. During the COVID-19 pandemic, non-pharmacological interventions increased the positive rate of both indoor and outdoor allergens in children. The sIgE grade of dust mite allergen and multiple sensitization rates were significantly higher than those before COVID-19.